MicroRNA‐539 functions as a tumour suppressor in prostate cancer via the TGF‐β/Smad4 signalling pathway by down‐regulating DLX1. Issue 9 (12th July 2019) - Sun, Baogang; Fan, Yingying; Yang, Aijun; Liang, Lunan; Cao, Jinghe
Abstract: Prostate cancer (PCa) is the second leading cause of cancer‐related death in males, primarily due to its metastatic potential. The present study aims to identify the expression of microRNA‐539 (miR‐539) in PCa and further investigate its functional relevance in PCa progression both in vitro and in vivo. Initially, microarray analysis was conducted to obtain the differentially expressed gene candidates and the regulatory miRNAs, after which the possible interaction between the two was determined. Next, ectopic expression and knock‐down of the levels of miR‐539 were performed in PCa cells to identify the functional role of miR‐539 in PCa pathogenesis, followed by the measurement of E‐cadherin, vimentin, Smad4, c‐Myc, Snail1 and SLUG expression, as well as proliferation, migration and invasion of PCa cells. Finally, tumour growth was evaluated in nude mice through in vivo experiments. The results found that miR‐539 was down‐regulated and DLX1 was up‐regulated in PCa tissues and cells. miR‐539 was also found to target and negatively regulate DLX1 expression, which resulted in the inhibition of the TGF‐β/Smad4 signalling pathway. Moreover, the up‐regulation of miR‐539 or DLX1 gene silencing led to the inhibition of PCa cell proliferation, migration, invasion, EMT and tumour growth, accompanied by increased E‐cadherin expression and decreased expression of vimentin, Smad4, c‐Myc, Snail1 and SLUG. In conclusion, the overexpression of miR‐539‐mediated DLX1 inhibition could potentially impede EMT, proliferation, migration and invasion of PCa cells through the blockade of the TGF‐β/Smad4 signalling pathway, highlighting a potential miR‐539/DLX1/TGF‐β/Smad4 regulatory axis in the treatment of PCa.